Growth, Safety Nets and Poverty : Assessing Progress in Ethiopia from 1996 to 2011 - Hill, Ruth Vargas; Tsehaye, Eyasu (World Bank, Washington, DC, 2018)
In the past 10 years, Ethiopia experienced high and consistent growth, invested in public goods provision to poor households, and saw impressive gains in well-being for many households. This paper exploits variation in sectoral growth and public goods provision across zones and time, to examine whether poverty reduction was driven by growth and provision of public goods and what type of growth -- growth in agriculture, manufacturing, or services -- was more effective at reducing poverty. The paper pays particular attention to controlling for other drivers of poverty reduction and instrumenting growth in a sector of particular policy focus -- agriculture -- to identify causal effects. The analysis finds that reductions in poverty were largest in places where agricultural output growth has been higher, safety nets have been introduced, and improvements in market access have been made. Agricultural output growth caused reductions in poverty of 2.2 percent per year on average post-2005, and 0.1 percent per year prior to 2005. The government's policy focus on stimulating productivity gains in smallholder cereal farmers contributed to this growth, but only when the weather was good, and prices were high. Access to markets was essential: agricultural growth reduced poverty in places close to urban centers, but not in remote parts of the country.